IDENTIFIKASI POTENSI INTERAKSI OBAT ANTIVIRUS PADA PASIEN TERDIAGNOSA COVID-19 di RSUD Prof. Dr. W.Z. JOHANES KUPANG - Fraga, Aurelia Da Silva Sequeira; Berkanis, Appolonaris; Lodo, Mirdo Albertho Rohi; Beama, Christin Aprilian (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
COVID-19 is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus. This virus was first identified in Wuhan, China and is one of the new species of Corona virus that can cause pneumonia and threaten the world because it spreads very quickly and causes death so that the WHO declared a pandemic status. Range COVID-19 occurs in patients with comorbid or comorbid conditions. Treatment of COVID-19 patients uses drugs such as antivirals, antibiotics, and immunomodulators. Concomitant use of antivirals and other drugs should be considered so as to prevent the possibility of Drug Related Problems such as drug interactions. The purpose of the study was to determine the potential interaction of antiviral drugs in COVID-19 patients at RSUD Prof. Dr. W.Z. Johanes Kupang. This study is an observational descriptive study that collected data retrospectively by looking at medical record data of patients diagnosed with COVID-19 with cardiovascular comorbidities. The population in this study is medical record data of patients diagnosed with COVID-19 who underwent hospitalization in 2022, which was 103 patients and samples obtained by 23 patients. Evaluation of drug interactions based on the mechanism of action and severity in patients shows that potential drug interactions occur pharmacodynamically (3 events) and pharmacokinetics (14 events) while based on severity shows the potential interactions occur at mild severity as many as 3 events and moderate as many as 14 events. Keywords: Antivirus, COVID-19, Comorbid, Drug related problem, Drug Interaction